MANEUVERING PERFORMANCE OF A FERRY AFFECTED BY RUDDER AREA AND SPEED - Muhammad, Andi Haris; Djabbar, Muhammad Alham; Yuniarsih, Nidia (The Indonesian Journal of Naval Architecture, 2013)
The aim of the study is to determine the effect of rudder area and speed on a ferry ship maneuvering performance, especially during the turning circle and zigzag maneuver. MATLAB-simulink was used to simulate turning circle and zigzag maneuver. The simulation utilized model based on the concept of Mathematical Modelling Group (MMG) includes testing/separating components of the hull equations, propeller and rudder as well as the interaction among them (hull, propeller and rudder). The result of simulation indicated that rudder dimension and ship speed affect both turning circle and zigzag maneuver of the ferry reasonably.